State intervention in the context of creative industries = Interwencjonizm państwowy w kontekście sektorów kreatywnych - Drab-Kurowska, Anna (Zielona Góra: Faculty of Economics and Management Press)
The aim of this article is to present the impact of state intervention on the development of the creative sector. The article attempts to identify the reasons why the state should lead to this kind of action. In addition, it pointed out possible areas of impact with regard to the way of influence. To achieve the objective pursued was used domestic and foreign-language specialist literature and reports of foreign institutions on the operation of creative sectors, and support were the observations of his own Polish creative sector.
Keywords: polityka gospodarcza; interwencjonizm; sektory kreatywne; economic policy; interventionism; creative industries